2017
DOI: 10.1158/1078-0432.ccr-16-3055
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Phase II Neoadjuvant Study of Cisplatin, Paclitaxel With or Without Everolimus in Patients with Stage II/III Triple-Negative Breast Cancer (TNBC): Responses and Long-term Outcome Correlated with Increased Frequency of DNA Damage Response Gene Mutations, TNBC Subtype, AR Status, and Ki67

Abstract: Background Due to inherent disease heterogeneity, targeted therapies have eluded TNBC, and biomarkers predictive of treatment response have not yet been identified. This study was designed to determine if the mTOR inhibitor everolimus with cisplatin and paclitaxel would provide synergistic anti-tumor effects in TNBC. Methods Stage II/III patients with TNBC were enrolled in a randomized phase II trial of preoperative weekly cisplatin, paclitaxel and daily everolimus or placebo for 12 weeks, until definitive s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 54 publications
(61 reference statements)
2
82
0
1
Order By: Relevance
“…Furthermore, we reported that the rate of pCR to NAC was 24.1% for TNBC AR+ group compared with 60% of QNBC group. These findings matched with voluminous previous reports (Hilborn et al, 2016;Gerratana et al, 2018;Masuda et al, 2013;Asano et al, 2016;Asano et al, 2017, andovanović et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, we reported that the rate of pCR to NAC was 24.1% for TNBC AR+ group compared with 60% of QNBC group. These findings matched with voluminous previous reports (Hilborn et al, 2016;Gerratana et al, 2018;Masuda et al, 2013;Asano et al, 2016;Asano et al, 2017, andovanović et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…In a recent randomized phase II trial to evaluate the NAC (cisplatin, paclitaxel ± everolimus) in 145 patients with TNBC showed that low expression level of AR was linked to higher pCR than higher AR levels. Moreover, the investigators demonstrated a lack of significant changes in AR levels (before, during or after NAC), suggesting that the chemotherapy did not affect AR expression (Ovanović et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Responses were limited to patients with NGS aberrations in PIK3CA, AKT, or PTEN. In the neoadjuvant setting, the addition of everolimus to cisplatin and paclitaxel did not increase pCR in molecularly unselected TNBC, and exploratory analyses showed that those who achieved pCR were not enriched for mutations in the PI3K/ AKT/mTOR pathway (47).…”
Section: ) Genomic Alteration (Frequency %)mentioning
confidence: 96%
“…Lehmann et al identified six distinct TNBC subtypes, each displaying a unique biology, with recent studies merging these into four transcriptionally defined subtypes (8,9). These subtypes, have been found to be associated with response to chemotherapy (2,8,10). Balko et al have further evaluated the molecular profiles of residual disease in patients with TNBC who received NeoCT and reported a variety of genomic alterations (mutations and copy number changes) including alterations in cell cycle, phosphoinositide 3-kinase (PI3K)/mTOR alterations, growth factor receptor amplifications, Ras/mitogen-activated protein kinase (MAPK) alterations, DNA repair alterations (11).…”
Section: Introductionmentioning
confidence: 99%